2017
DOI: 10.1002/ajim.22776
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and chronic obstructive pulmonary disease in Minsk tractor plant workers

Abstract: Workers in highly exposed to dust workplaces had double odds of developing COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…6 Interestingly, almost similar magnitude of effect was found in specific populations, like miners, when highly exposed workers are compared to those with low exposure, 7 or tractor plant workers. 23 In our multiple regression model, the strength of effect associated with occupational exposure may be as high as the one of smoking, and this will dictate Abbreviations: VGDF, vapors, gases, dusts and fumes; SHS, secondhand smoke; COPD, chronic obstructive pulmonary disease; OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…6 Interestingly, almost similar magnitude of effect was found in specific populations, like miners, when highly exposed workers are compared to those with low exposure, 7 or tractor plant workers. 23 In our multiple regression model, the strength of effect associated with occupational exposure may be as high as the one of smoking, and this will dictate Abbreviations: VGDF, vapors, gases, dusts and fumes; SHS, secondhand smoke; COPD, chronic obstructive pulmonary disease; OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it was reported that the prevalence of chronic bronchitis is 18.1% in former coal miners in Ukrainian [ 20 ]. And plenty studies demonstrated that the presence of COPD was significantly associated with occupational exposures [ 9 , 20 , 22 ], it was estimated that 10–15% of the total burden of COPD is associated with workplace exposures to dusts, noxious gases/vapors, and fumes [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We defined occupational exposure as exposure to dust, gases/fumes, insecticides, chemical substances, paints, and metals at work for at least 8 hours per day for more than 1 year. [13][14][15] The COPD Assessment Test (CAT), a validated eightquestion health-status instrument, includes cough, phlegm, chest tightness, shortness of breath, limited at home, confidence leaving home, sound sleep, and energy, with scores ranging from 0 to 5. 16 The total score is calculated by simply adding all scores, with higher scores indicating greater symptom severity.…”
Section: Measurementmentioning
confidence: 99%